Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Berbatuan Crossword Puzzle Terhadap Keaktifan Belajar Siswa Pada Materi Pendidikan Agama Islam di SMP N 3 Koto Baru Kabupaten Dharmasraya - Riri Anggia Rovi; Supratman Zakir; Darul Ilmi; Iswantir M (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research was conducted because researchers found that teachers only apply conventional learning models (lectures) so that educators talk more than students. In addition, students rarely pay attention and record the teacher's explanation. Then there was no feedback from students during the question and answer session, and they did not have the courage to express their opinions. The purpose of this study was to determine the effect of the Crossword Puzzle Assisted Team Games Tournament (TGT) Cooperative Learning Model on Student Learning Activeness in PAI Material at SMP N 3 Koto Baru, Dharmasraya Regency. This type of research is quantitative, using Quasy Experiments. The population of this study were all students of class VIII, totaling 40 people. The sampling technique used was to collect UTS values, then normality and homogeneity tests were carried out, then the samples were determined randomly. Data collection using a questionnaire. The analysis technique uses the t-test. The results showed that the average student activity in the experimental class was 112.20 and that of the control group was 77.20. The results of the analysis using the Independent Sample T-test between experimental and control classes obtained a t-count of 10.014 and a t-table of 2.024, and a significance level of 0.000. So it can be concluded that the activeness of students using the Crossword Puzzle-assisted Team Games Tournament (TGT) is better than students using the conventional model (teaching) in class VIII SMP N 3 Koto Baru.